PENGUATAN KAPASITAS USAHA MIKRO MELALUI LITERASI DIGITAL MARKETING DAN KEWIRAUSAHAAN DI DESA NGEPER - saida, ita aristia saida; Tawakkal, M. Iqbal (Badan Usaha Milik Desa Berkaho Pungpungan, 2025)
This community service program aims to enhance the capacity of Micro, Small, and Medium Enterprises (MSMEs) in Ngeper Village, Padangan District, Bojonegoro Regency through entrepreneurship and digital marketing literacy training. The program was implemented in several stages: preparation, socialization, training, and evaluation. The two-day training employed a participatory and practical approach, covering topics such as basic entrepreneurship, digital content creation, utilization of social media and marketplaces, and setting up Google Business Profiles. The results show that the training was highly relevant to the participants’ needs, with a satisfaction rate of 92%. The program positively impacted participants' understanding and skills in digital product marketing. As a follow-up, a communication group was formed, and further training and the establishment of a digital MSME community in Ngeper Village are planned.